Production Potential of Maize (Zea mays L.)- Based Intercropping Systems under Foothill Condition of Nagaland - Kithan, Lowrence; Longkumer, L. Tongpang (International Journal of Bio-resource and Stress Management, 2017)
A study was conducted on Production potential of Maize (Zea mays L.)- Based Intercropping systems at the experimental farm of School of Agricultural Sciences and Rural Development (SASRD) Nagaland University, Medziphema Campus, under rainfed condition during 2015 and 2016. The treatments comprised of different row ratios i.e. (1:1), (1:2), (2:1) and (2:2) respectively of maize intercropped with perilla, sesame, ricebean and soybean. The experiment was laid in RBD with 3 replications and 21 treatments. Sole maize recorded the best with regard to growth parameters like plant height, leaf area plant-1 and stem thickness with its pooled at 315.25 cm, 2.23 and 2.44 cm. While in regard to yield parameters sole maize recorded superior than all other sole crops with its pooled in respect to number of cobs plant-1 (1.92), cob weight (g) (144.17 g), number of grains cob-1 (555.67), shelling percentage (80.83), grain yield (4280.06 kg ha-1) and stover yield (5296.82 kg ha-1). Among the different intercropping systems paired rows (2:2) ratios of maize+soybean performed significantly better in terms of yield with pooled of (1565.65 kg ha-1) and production efficiencies viz., LER (1.78, 1.78), RCC (53.95, 55.22), CEY (4692.63 kg ha-1, 4701.3 kg ha-1), ATER (1.53, 1.53), Aggressivity (0.04, 0.041) and SPI (75.36, 77.20). As for economics, paired rows (2:2) ratios of maize+ soybean proved superior to all other treatments in net return (Rs. 1,42,612.6, Rs. 1,44,779.4), gross return (Rs. 1,72,612.6, Rs. 1,74,779.4) and B:C ratio (4.75 and 4.82).